(untitled) (PJDOL, 2023)
The study explored views of teachers about relationship between social behaviour and academic performance. The objectives of the study were to examine the effects of social behaviour on academic performance; compare academic results of students with social behaviour; investigate the importance of social behaviour on academic performance; and, suggest what necessary steps should be taken to improve the academic performance and social behaviour.